An Equivalent Fiber Frame Model for Nonlinear Analysis of Masonry Structures. Issue 4 (3rd April 2021) - Yousefi, Behrooz; Soltani, Masoud
ABSTRACT: In this study, an equivalent fiber frame model based on an analytical method is proposed for masonry structures assessment. The equivalent frame model (EFM) is a simple applicable approach that is relatively accurate and bears a low computational cost. It holds proper convergence and adaptability compared to micro modeling methods. The progression of nonlinearity over the cross-section and along the height of masonry walls is simulated by proposed homogenized constitutive models. Moreover, a new procedure is proposed for the evaluation of unreinforced masonry walls strengthened with reinforced concrete layers. To examine the shear behavior (bed joint sliding mode of failure, and diagonal tension mode), an interface element based on a smeared crack approach is developed. Finally, the accuracy of the suggested approach is verified through a comparison of available experimental results and existing analytical methods.